Artificial Intelligence of Things (AIoT) To Improve Efficiency and Automation in Industrial 4.0 - Devi Rahmayanti (MES Bogor, 2024)
The integration of Artificial Intelligence (AI) and the Internet of Things (IoT), popularly known as Artificial Intelligence for Everything (AIoT), has become a game-changing technology for industrial use. This research explores how AIoT enhances automation and efficiency in industrial machinery through networked devices, real-time decision-making, and advanced data analytics. Through a thorough analysis of recent studies and academic publications, the paper emphasizes the potential of AIoT in intelligent monitoring systems, process optimization, and predictive maintenance. The findings reveal that AIoT enables industrial machines to operate autonomously by leveraging AI algorithms to analyze data collected from IoT devices. This integration reduces downtime, optimizes resource utilization, and improves overall operational efficiency. Furthermore, the study emphasizes the role of edge computing and cloud-based platforms in facilitating seamless data processing and decision-making in real-time. Key challenges such as data security, system scalability, and implementation cost are also identified, along with potential strategies to address these issues. This research provides valuable insights for industry stakeholders, policy makers, and researchers interested in leveraging AIoT to revolutionize industrial operations and achieve Industry 4.0 goals.